2013
DOI: 10.1371/journal.pone.0073976
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Isolation between Host Races of Phytomyza glabricola on Ilex coriacea and I. glabra

Abstract: Recently diverged taxa often show discordance in genetic divergence among genomic loci, where some loci show strong divergence and others show none at all. Genetic studies alone cannot distinguish among the possible mechanisms but experimental studies on other aspects of divergence may provide guidance in the inference of causes of observed discordances. In this study, we used no-choice mating trials to test for the presence of reproductive isolation between host races of the leaf-mining fly, Phytomyza glabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…At least one reproductive isolating barrier, immigrant inviability, is related to host use (Herbert et al. ), and a recent genome scan suggests that several loci have experienced host‐associated selection (Hebert et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least one reproductive isolating barrier, immigrant inviability, is related to host use (Herbert et al. ), and a recent genome scan suggests that several loci have experienced host‐associated selection (Hebert et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Though a lack of genetic structure among mitochondrial sequences suggests that this shift has been relatively recent (Scheffer and Hawthorne ), attempts to produce hybrid offspring have failed (Hebert et al. ), so it remains possible that these flies are already different “species” that could have differentiated before one of them shifted to a new host (Fig. C).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that hybridization of flies from the respective host plants has a 100% failure rate in the laboratory, indicating some measure of reproductive isolation that may carry into the field (Hebert et al. ). However, no host‐associated divergence in mitochondrial sequences has been found (Scheffer and Hawthorne ), suggesting that the nuclear sequence and AFLP divergence are recent or that some gene flow may occur in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these phenological differences, adult P. glabricola from both hosts emerge in synchrony once a year in mid‐January to mid‐February, potentially allowing mating of flies from the two host plant species (Scheffer ), although laboratory mating experiments produced no adult fly hybrid offspring (Hebert et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation